Avaliação técnico-econômica de um processo para produção de diesel renovável com fornecimento alternativo de hidrogênio - Lunardi, Pietro Machado (2024)
The hydrodeoxygenation of triglycerides and fatty acids (HEFA) represents a well-established technological pathway for producing renewable drop-in fuels, such as renewable diesel, aviation fuel, or renewable light ends, like naphtha and LPG. A reliable hydrogen supply is required, and the conventional method involves steam methane reforming (SMR). This research proposes an integrated process that simultaneously evaluates hydrodeoxygenation (HDO) and hydrogen production. Two scenarios are compared by process simulation, equipment sizing, and economic analysis: one with traditional SMR (SC-A) and another with electrified SMR (SC-B). The HDO capacity was 6220 barrels per day (38.000 kg/hr) of soybean oil, and the average yields for renewable diesel, naphtha, and LPG were 71.23 %-wt, 1.80 %-wt, and 5.87 %-wt, accordingly. The electrified SMR required about 9,73 MWh/ton of hydrogen. The SC-B technology arrangement does not require natural gas; begin fuel and steam self-sufficient. The Internal Rate of Return (IRR) of SC-A versus SC-B was 33.28% x 7.89%, while the Discounted Payback Period (DPP) was 2.0 x 10.2 years. Finally, both systems resulted in technical and economic feasibility. Nevertheless, the Monte-Carlo assessment suggests more economic risk for the second one.